New records of harvestmen (Arachnida, Opiliones) from Minnesota, USA - Shoemaker, A. Kenji; Burns, Mercedes; Boyer, Sarah L. (Zootaxa, 2017)
Harvestmen (Opiliones) are a diverse order of arachnids composed of more than 6,600 described species which together span an almost global distribution. Although these animals may occur in extremely high abundance in both pristine and disturbed habitats, much of harvestman diversity remains undescribed, undocumented, and/or in need of taxonomic attention. In the current study, we focus on the harvestman diversity of the state of Minnesota, USA, where a lack of local expertise and effort has left the species richness of the state largely undocumented. We document two genera and seven species previously unrecorded in the state.—Leiobunum aldrichi, L. calcar, L. flavum, L. politum, L. ventricosum, L. vittatum, and Odiellus pictus.